Measurement of W-pair cross sections in e+e− interactions at √s = 172 GeV and W-decay branching fractions - Dova, María Teresa (1997)
We report on the measurement of W-boson pair-production with the L3 detector at LEP at an average centre-of-mass energy of 172.13 GeV. In a data sample corresponding to a total luminosity of 10.25 pb−1 we select 110 four-fermion events with pairs of hadronic jets or leptons with high invariant masses. Branching fractions of W decays into different fermion-antifermion pairs are determined with and without the assumption of charged-current lepton universality. The branching fraction for hadronic W decays is measured to be: B(W → hadrons) = 64.2+3.7−3.8 (stat.) ± 0.5 (syst.) %. Combining all final states the total cross section for W-pair production is measured to be: σWW = 12.27+1.41−1.32 (stat.) ± 0.23 (syst.) pb. The results are in good agreement with the Standard Model.